V-bend die forming performance of oil palm fiber composite - Dhar Malingam, Sivakumar; Che Mahzan, Muhammad ‘Ammar; Said, Md Radzai; Rivai, Ahmad; Nordin, Mohd Nur Azmi; Selamat, Mohd Zulkefli; Subramonian, Sivarao (Trans Tech Publications Ltd., 2015)
Composite materials have steadily gained recognition worldwide for its uses in various sectors such as aerospace, infrastructures and automotive industries. In stamp forming of V-bend die, the most sensitive feature is elastic recovery during unloading called spring-back. This phenomenon will affect bend angle and bend curvature. This research studies the effects of tool radius, feed rate, temperature and weight ratio of fiber to Polypropylene on the spring-back of palm fiber composite. Analyzed results obtained from Design of Experiment (DOE) shows temperature, fiber composition followed by feed rate gives significant effect towards spring-back. The suggested temperature, fiber composition and feed rate to get the smallest spring-back angle in the current study are 150°C, 30wt% and 500mm/min.